2022
DOI: 10.3390/nu14081622
|View full text |Cite
|
Sign up to set email alerts
|

Oral Intake of Chicken Bone Collagen Peptides Anti-Skin Aging in Mice by Regulating Collagen Degradation and Synthesis, Inhibiting Inflammation and Activating Lysosomes

Abstract: The effect of diet on skin aging has become an interesting research topic. Previous studies have mostly focused on the beneficial effects of collagen peptides derived from marine organisms on the aging skin when administered orally, while the beneficial effects of collagen peptides derived from poultry on aging skin have been rarely reported. In this study, collagen peptides were prepared from chicken bone by enzymatic hydrolysis, and the effect and mechanism of action of orally administered collagen peptides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…Oral intake of porcine placenta extract can improve human skin quality and increase skin elasticity, hydration and barrier functions [ 3 ]. Oral intake of chicken bone collagen peptides can improve the condition of aging skin in mice, including maintaining a smooth, orderly, and complete structure and increasing the dermal thickness and collagen content [ 7 ]. Our results showed that the skin structure of CPE mice was similar to that in healthy mice, and no obvious pathological damage was found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oral intake of porcine placenta extract can improve human skin quality and increase skin elasticity, hydration and barrier functions [ 3 ]. Oral intake of chicken bone collagen peptides can improve the condition of aging skin in mice, including maintaining a smooth, orderly, and complete structure and increasing the dermal thickness and collagen content [ 7 ]. Our results showed that the skin structure of CPE mice was similar to that in healthy mice, and no obvious pathological damage was found.…”
Section: Discussionmentioning
confidence: 99%
“…Oral intake of porcine placenta extract can improve human skin quality and increase skin elasticity, hydration and barrier function [ 3 ]. Oral intake of chicken bone collagen peptides anti-skin aging in mice by regulating collagen degradation and synthesis, inhibiting inflammation and activating lysosomes [ 7 ]. In addition, studies have evidenced that the main bioactive substances of placenta extract are polypeptides, which have favorable antioxidant activity [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mouse models of skin aging were established in current study by treatment with D-gal/UVB as previously described (Jiayi et al, 2019;Zhang et al, 2020;Cao et al, 2022). Chronic injection of D-gal, a reducing sugar, results in oxidative stress including reductions of antioxidant enzymes, inflammation and apoptosis, mimicking a natural aging process (Shen et al, 2002;Shan et al, 2009;Chen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…D-gal and UVB co-treatment induces a large-scale burst of free radicals, leading to the oxidative damage in the skin and skin aging-like symptoms such as wrinkling, sagging, dryness, and erythema (Zhang et al, 2020). This animal model has been widely used to elucidate cellular and molecular changes that may have a causal role in skin aging, and to screen anti-aging drugs (Jiayi et al, 2019;Zhang et al, 2020;Cao et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Collagen peptide supplements are made of hydrolyzed collagen/gelatin that have been degraded into individual amino acids and smaller peptides with a lower molecular weight compared to native collagen (3-6 versus 285-300 kDa, respectively). The lower molecular weight allows for transport of small intact peptides (bioactive peptides) into circulation, which are thought to boost endogenous collagen synthesis [1,7]. Collagen peptide supplements have been demonstrated to enhance collagen synthesis by fibroblasts in the ECM, thereby repairing photodamage in skin and reducing joint pain and inflammation in individuals suffering from osteoarthritis and connective tissue injuries [8].…”
Section: Introductionmentioning
confidence: 99%